The Nucleophilicity of Persistent α‐Monofluoromethide Anions. Issue 41 (15th September 2016) - Zhang, Zhe; Puente, Ángel; Wang, Fang; Rahm, Martin; Mei, Yuncai; Mayr, Herbert; Prakash, G. K. Surya
Abstract: α‐Fluorocarbanions are key intermediates in nucleophilic fluoroalkylation reactions. Although frequently discussed, the origin of the fluorine effect on the reactivity of α‐fluorinated CH acids has remained largely unexplored. We have now investigated the kinetics of a series of reactions of α‐substituted carbanions with reference electrophiles to elucidate the effects of α‐F, α‐Cl, and α‐OMe substituents on the nucleophilic reactivities of carbanions. Abstract : Although α‐fluorocarbanions are key intermediates in nucleophilic fluoroalkylation reactions, the α‐fluorine effect on the reactivity of the carbanions has remained largely unexplored. Kinetic studies have now revealed that α‐monofluorine substitution of the carbanions significantly enhances their nucleophilicity.